Limit Cycles and Invariant Curves in a Class of Switching Systems with Degree Four - Xinli Li; Huijie Yang; Binghong Wang (Journal of Function Spaces)
In this paper, a class of switching systems which have an invariant conic x2+cy2=1,c∈R, is investigated. Half attracting invariant conic x2+cy2=1,c∈R, is found in switching systems. The coexistence of small-amplitude limit cycles, large amplitude limit cycles, and invariant algebraic curves under perturbations of the coefficients of the systems is proved.